Effect of epoxy resin sealing on corrosion resistance of arc spraying aluminium coating using cathode electrophoresis method. (29th January 2018) - Pang, Xuming; Wang, Runqiu; Wei, Qian; Zhou, Jianxin
Abstract: Arc-sprayed Al coating was sealed with epoxy resin using the cathode electrophoresis method. The anti-corrosion performance of the coatings sealed with epoxy resin was studied by means of a 3.5 wt.% NaCl solution test at 40 °C. For comparison, the anti-corrosion performance of Al coating sealed with boiling water was also performed under the same conditions. The results show that epoxy resin with a thickness of about 20 microns can entirely cover open pores and decreases the surface roughness of the as-sprayed Al coating, and the epoxy resin even permeates into the gaps among lamellar splats from open pores. After corrosion, the thickness of the epoxy resin layer is unchanged and can still cover the as-sprayed Al coating entirely. However, the thickness of Al coating sealed with boiling water decreases from 100 to 40 microns, which indicates that the arc-sprayed Al coating has much better corrosion resistance than the Al coating sealed with boiling water. Meanwhile, the content of substituted benzene ring in the epoxy resin increases, but aromatic ring decreases according to the fourier transform infrared spectra, which will cause the rigidity of the epoxy resin to increase, but the toughness slightly decreases after corrosion.